Evaluating the impact of task-sequencing on cognitive and motor performance in MS: PASAT and 3-minute walk test order effects - Siegert, Valentin; Köhler, Laura J.; Schreff, Lucas; Hamacher, Daniel; Oschmann, Patrick; Rothhammer, Veit; Keune, Philipp M.; Müller, Roy (Frontiers in Neurology, 2025)
IntroductionCognitive-motor functioning in persons with Multiple Sclerosis (PwMS) may be studied effectively by means of dual-task paradigms, under which potential impairments may become more salient. However, the influence of task sequencing, i.e., the order in which a cognitive or motor task is administered prior to the dual-task condition remains unclear. This study aimed to investigate potential task-sequencing effects, as reflected in fatigue or learning effects across single- and dual-task conditions.MethodsA total of 152 PwMS with an average EDSS of 2.3 were quasi-randomly assigned to six groups. The groups differed in the sequence in which a single-motor-task (3-min-25-foot-walk) and a single-cognitive-task (Paced Auditory Serial Addition Test, PASAT) as well as a dual-task combining both were administered. Gait parameters were measured using an IMU sensor. Statistical analyses compared single- and dual-task performance depending on task-sequencing.ResultsTask-sequencing did not affect cognitive or motor performance during the dual-task condition. However, a significant improvement in PASAT scores was observed between the first and second single-task trials, indicating a learning effect. No significant fatigue effects were found in gait parameters between repeated single-task trials.DiscussionThe findings suggest that the sequence of task administration does not significantly influence dual-task performance in the subgroup of PwMS focused on in the current work. Merely repeated single-task use of the PASAT leads to cognitive performance improvements, likely due to learning effects. These results indicate that, in clinical settings, test order may be of minor importance for dual-task conditions, if administered according to the procedure used in the current work.